Pleiotropic neurotransmitters: neurotransmitter-receptor crosstalk regulates excitation-inhibition balance in social brain functions and pathologies - Anping Chai (Frontiers in Neuroscience)
Neuronal excitation-inhibition (E/I) balance is essential for maintaining neuronal stability and proper brain functioning. Disruptions in this balance are implicated in various neurological disorders, including autism spectrum disorder, schizophrenia and epilepsy. The E/I balance is thought to be primarily mediated by intrinsic excitability, governed by an array of voltage-gated ion channels, and extrinsic excitability, maintained through a counterbalance between excitatory synaptic transmission primarily mediated by excitatory transmitter glutamate acting on excitatory ion-tropic glutamate receptors and inhibitory synaptic transmissions chiefly mediated by GABA or glycine acting on their respective inhibitory ion-tropic receptors. However, recent studies reveal that neurotransmitters can exhibit interactions that extend beyond their traditional targets, leading to a phenomenon called neurotransmitter-receptor crosstalk. Examples of such crosstalks include earlier discovery of inhibitory glycine functioning as co-transmitter gating on the NMDA subtype of excitatory glutamate receptor, and the most recent demonstration that shows the excitatory glutamate transmitter binds to the inhibitory GABAA receptor, thereby allosterically potentiating its inhibitory function. These studies demonstrate structurally and physiologically important crosstalk between excitatory and inhibitory synaptic transmission, blurring the distinction between the concepts of classic excitatory and inhibitory synaptic transmission. In this article, evidence supporting the forms of excitatory and inhibitory crosstalks will be briefly summarized and their underlying mechanisms will be discussed. Furthermore, this review will discuss the implications of these crosstalks in maintaining the E/I balance, as well as their potential involvement in synaptic plasticity and cognition in the context of social conditions.